A demographic profile of cervical injury: an Indonesian single tertiary hospital study with 6 months to 1-year follow-up - Lukas Widhiyanto, LUK (Springer Nature, 2021)
Background Spinal cord injury (SCI) can cause considerable morbidity and mortality. Until now there is no spinal cord injury profile in Indonesia. Therefore, this study aims to provide an overview of the spinal cord injury profile as well as to analyze the functional outcome at the sixth month and the first year.